Side differences of upper quarter Y balance test performance in sub-elite young male and female handball players with different ages - Bauer, J., Panzer, S.; Muehlbauer, T. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background Handball is characterised by repetitive passing and shooting actions mainly performed with the throwing arm. This can lead to side differences (inter-limb asymmetry) in upper quarter mobility/stability between the throwing and non-throwing arm, which could even increase with advancing age (i.e., playing experience). However, side differences in upper quarter mobility/stability is associated with an increased musculoskeletal injury risk. Therefore, we assessed side differences in upper quarter mobility/stability in young handball players at different ages using a cross-sectional study design.